2011
DOI: 10.3109/13880209.2011.560161
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and antimicrobial activities of branches extracts of fiveJuniperusspecies from Turkey

Abstract: The results give a scientific basis to the traditional utilization of these Juniperus species, also demonstrating their potential as sources of natural antioxidant and antimicrobial compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 30 publications
4
37
1
1
Order By: Relevance
“…Nevertheless, Keskes et al 14 reported the methanol extract to show a stronger ability to scavenge DPPH radicals (EC 50 value = 2 μg mL −1 ). Taviano et al 35 studied the antioxidant activity of methanol and water extracts of five different Turkish Juniperus species, which showed a weaker activity in comparison with the herein studied extracts. On the other hand, the C. cinerea infusion extract demonstrated a higher DPPH radical scavenging activity (EC 50 = 24.8 ± 0.2 µg mL −1 ) in comparison with its hydroethanolic extract (EC 50 = 26.0 ± 0.1 µg mL −1 ), contrary to what happened for all the remaining methods for both species.…”
Section: Antioxidant Activitymentioning
confidence: 84%
“…Nevertheless, Keskes et al 14 reported the methanol extract to show a stronger ability to scavenge DPPH radicals (EC 50 value = 2 μg mL −1 ). Taviano et al 35 studied the antioxidant activity of methanol and water extracts of five different Turkish Juniperus species, which showed a weaker activity in comparison with the herein studied extracts. On the other hand, the C. cinerea infusion extract demonstrated a higher DPPH radical scavenging activity (EC 50 = 24.8 ± 0.2 µg mL −1 ) in comparison with its hydroethanolic extract (EC 50 = 26.0 ± 0.1 µg mL −1 ), contrary to what happened for all the remaining methods for both species.…”
Section: Antioxidant Activitymentioning
confidence: 84%
“…Ball. (Jom)) from Turkey by Taviano et al (2011). Both in DPPH and TBA test, Jom resulted the most active (IC 50 = 0.034 ± 0.002 mg/ml and 0.287 ± 0.166 µg/ml, respectively).…”
Section: The Contents Of Total Phenols and Total Flavonoids And Dpph mentioning
confidence: 89%
“…For example, Pinus nigra (tar, resin, and gum) exhibited strong antimicrobial [55], wound healing [56], and antiparasitic [57] activity properties. Allium sativum was found to have antibacterial [31] and antiparasitic [32][33][34] effects. Rhus coriaria was found to have potent antibacterial [35] and antioxidant properties [36].…”
Section: Discussionmentioning
confidence: 99%